Broken promises and breaking ground for responsible innovation – intervention research to transform business-as-usual in nanotechnology innovation. Issue 6 (2nd July 2016) - Wiek, Arnim; Foley, Rider W.; Guston, David H.; Bernstein, Michael J.
ABSTRACT: Despite repeated calls for novel forms of innovation and governance, including responsible innovation, anticipatory governance, and sustainability-oriented governance, nanotechnology continues to be mainly innovated following conventional schemes – with persistent shortcomings and negative impacts. Shifting these schemes towards sustainable and responsible innovation and fully utilising the benefits of sustainable nanotechnologies will necessitate difficult changes across all stages of and actors in the innovation process. We outline an agenda for intervention research in support of such changes. The article synthesises insights from four years of research on nanotechnology innovation, anticipatory governance, and sustainability in urban environments, with a focus on Phoenix, Arizona.